Experimental Study of the Operational Parameters on Low-cost Single-basin Solar Still in Jessore, Bangladesh - Biswasa, Biplob Kumar; Halima, Md Abdul; Parvina, Shahanaz; Mandala, Bablu Hira; Rahman, Md Wasikur; Alama, Md Jahangir; Islamb, Kh Md Shafiul (Journal of Chemical Engineering, 2017)
Keeping in mind the growing concern of sustainability, the present study aims to develop a hands-on technique for potable water production by using a portable single-basin solar still, which is constructed with low-cost, locally available and lightweight materials. The performance of single-basin solar still were investigated using different essential operational variables, which include weather condition, water salinity, brine water depth, and addition of glass marbles as energy absorbing material. Ambient weather conditions were found to have direct effect on the productivity of the still. The solar still productivity increased by 29% when a layer of glass marbles was used. The study also showed that the daily water production increased with the decrease in the initial depth of brine water. Estimating a useful life of 4 years of the solar still, an average cost of produced potable water was defined to be BDT 0.35 per lit. In addition, some important water quality parameters were tested and compared with drinking water standard values. The obtained values were found to be in line with the drinking water standards of WHO. Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 3-8